2018
DOI: 10.1590/1983-40632018v4851446
|View full text |Cite
|
Sign up to set email alerts
|

Crop rotation, green manure and nitrogen fertilizers in upland rice under no-tillage

Abstract: The Brazilian Savannah region presents a great potential for the expansion of upland rice crops. However, studies are necessary to identify practices that can improve the crop performance, especially in no-tillage systems. This study aimed to assess the effect of cover crops in association with corn on the development and yield of rice cultivated in rotation and cover fertilized with nitrogen doses. The sprinkler irrigation system was used and the experiment was developed in the 2014/2015 and 2016/2017 harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Arf et al. () reported that an increased NP may promote competition for nutrients, being insufficient for adequate filling of the grains and reducing their mass.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Arf et al. () reported that an increased NP may promote competition for nutrients, being insufficient for adequate filling of the grains and reducing their mass.…”
Section: Resultsmentioning
confidence: 99%
“…This result could be attributed to the lower N nutrition of the rice, indicated by the lower foliar content of the nutrient, as well as the lower accumulation of DMRP. Several studies have demonstrated the important role of N in the development, production components, and grain yield of upland rice (Arf et al, 2018;Fageria, Moreira, & Coelho, 2011;Kamara et al, 2010;Lacerda & Nascente, 2016;Reis et al, 2018).…”
Section: Rice Production and Productivity Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recommended N fertilizer rates for monocropped upland rice have been established (Cantarella et al, 1997). However, there is no N fertilizer recommendation for intercropping systems, especially in NTS (Nascente et al, 2013;Arf et al, 2018). We can infer that the current recommended N fertilizer rate may be insufficient to optimize grain yield of rice and biomass and CP in intercropped forage grasses.…”
Section: Forage Characteristics and Estimated Meat Productionmentioning
confidence: 97%